Inkjet Printing of Liquid Silicon. Issue 23 (7th December 2020) - Masuda, Takashi; Nakayama, Maui; Saito, Kimihiko; Katayama, Hirotaka; Terakawa, Akira
Abstract : Front Cover : In article number 2000362 by Takashi Masuda and co‐workers, a precursor solution for semiconducting Si called liquid‐Si is synthesized and printed by an inkjet method. Well‐defined printed patterns are converted into amorphous or polycrystalline Si by heat treatment. The Si printing technology is also extended to p‐ and n‐type Si film by synthesizing liquid‐Si chemically doped with B and P compounds, respectively.